Magnitude, characteristics and consequences of topical steroid misuse in rural North India: an observational study among dermatology outpatients. Issue 5 (18th May 2020) - Thomas, Molly; Wong, Celestine C; Anderson, Pam; Grills, Nathan
Abstract : Introduction: Current evidence indicates an alarming increase in topical steroid (TS) misuse in India. Data regarding the magnitude and characteristics of this problem in rural India, where 68% of the population resides, are insufficient. This study analyses the magnitude, causes, characteristics and consequences of TS misuse in rural India. It also examines the association between TS misuse and patients' perception of skin disease. Methods: A mixed-method observational study was conducted among the attendees of the dermatology outpatient department in a rural North Indian hospital. Those with a history of TS misuse were analysed for behaviour patterns and outcome. Results: Out of 723 patients, 213 (29.2%) misused TS. Clobetasol propionate (58.2%) was most commonly misused. Seventy brands of inappropriate fixed drug combination steroid creams were recovered from the patients. Pharmacists and local healers together contributed to 78% of the sources for steroid misuse. Almost 58% of participants perceived their skin conditions to be allergic reactions to food, when in fact 70.1% were tinea, 10% scabies and 9% acne. Eighty per cent of the respondents having tinea had tinea incognito and 97% had extensive lesions. Eighty-five per cent of the participants with scabies had atypical lesions and 80% with acne had steroid rosacea or aggravation of acne. The median expenditure incurred in purchasing these potentially harmful steroid creams was Rs 1000 (US14.1, equivalent to 3 days' wages of a labourer). Conclusion: Steroid misuse is a problem of epidemic proportion in rural India. This practice is changing the profile of many common and infective skin conditions, which portends diagnostic dilemmas and therapeutic challenges for clinicians. Misconceptions about skin disease drive the public to seek 'quick fixes' from non-allopathic providers who have unrestricted access to potent steroids. There is an urgent need to tighten regulatory controls over the manufacturing, sale and prescription of irrational TS combinations.